UPAYA IRAN BERGABUNG DENGAN SHANGHAI COOPERATION ORGANISATION (SCO) - Pramudya Pratama; Mhd. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Shanghai Cooperation Organisation (SCO) is a multilateral organization formed in 2001 by the People's Republic of China, Russia, Kazakhstan, Kyrgyzstan, and Tajikistan. At the beginning of its establishment the SCO aimed to solve the problem of national boundaries between SCO member states. In its development, SCO has entered other fields, such as economics, politics, culture and technology. SCO is a young organization that has extraordinary potential, especially in the economic field. Iran is a middle eastern country rich in its natural resources, especially oil and gas. In its development, Iran often experiences ups and downs in its economy, this is due to the many sanctions imposed by western countries, especially the United States. Therefore, Iran during the Ahmadinejad era initiated a policy of "look to the east" which meant that Iran changed the direction of its country's cooperation to non-western countries. SCO is included in this policy agenda, this is because SCO is a non-western organization that has a myriad of potentials in both the economic and political fields. This study aims to explain how Iran's efforts to join the SCO. This research uses qualitative research methods and uses secondary data collected from various sources which the author will then describe simply and systematically in sentence form. The results of the study concluded that Iran made various attempts to become a member of the SCO. Iran has repeatedly received pushback from the SCO but in 2021 after several changes in Iran's stance on international relations, Iran's accession into the SCO was accepted after more than 15 years as an observer member. Keywords: SCO, Iran, Look to the East, efforts, Economy, Politics